Viral inosine triphosphatase: A mysterious enzyme with typical activity, but an atypical function. (20th January 2021) - James, Amy M.; Seal, Susan E.; Bailey, Andy M.; Foster, Gary D.
Abstract: Plant viruses typically have highly condensed genomes, yet the plant‐pathogenic viruses Cassava brown streak virus, Ugandan cassava brown streak virus, and Euphorbia ringspot virus are unusual in encoding an enzyme not yet found in any other virus, the "house‐cleaning" enzyme inosine triphosphatase. Inosine triphosphatases (ITPases) are highly conserved enzymes that occur in all kingdoms of life and perform a house‐cleaning function by hydrolysing the noncanonical nucleotide inosine triphosphate to inosine monophosphate. The ITPases encoded by cassava brown streak virus and Ugandan cassava brown streak virus have been characterized biochemically and are shown to have typical ITPase activity. However, their biological role in virus infection has yet to be elucidated. Here we review what is known of viral‐encoded ITPases and speculate on potential roles in infection with the aim of generating a greater understanding of cassava brown streak viruses, a group of the world's most devastating viruses. Abstract : What we know and do not know about the inosine triphosphatase Ham1 found in the viruses causing cassava brown streak disease, namely cassava brown streak virus and Ugandan cassava brown streak virus.